Atrial fibrillation and Wolff–Parkinson–White syndrome: A double blow for the cardiologist. Issue 7 (14th July 2022) - Bazoukis, George; Papasavvas, Elias; Pavlou, Marios; Georgiou, Panagiota; Kapetis, Lorentzos; Patestos, Dimitrios; Vlachos, Konstantinos; Saplaouras, Athanasios; Letsas, Konstantinos P.; Efremidis, Michael; Tsielepis, Michalis
Abstract: Electrocardiographic findings including irregularity of the rhythm, a very rapid ventricular response, and the presence of a delta wave should raise the suspicion of pre‐excited atrial fibrillation with a rapid ventricular response. Urgent cardioversion is needed due to the risk of sudden cardiac death. Abstract : Electrocardiographic findings including irregularity of the rhythm, a very rapid ventricular response, and the presence of a delta wave should raise the suspicion of pre‐excited atrial fibrillation with a rapid ventricular response. Urgent cardioversion is needed due to the risk of sudden cardiac death.